Bioengineering and omics approaches for Type 1 diabetes practical research: advancements and constraints - Xi Peng; Ling Li; Yihua Peng; Guangju Zhou; Zhenmei An (Annals of Medicine)
Insulin dependency arises from autoimmunity that targets the β cells of the pancreas, resulting in Type 1 diabetes (T1D). Despite the fact that T1D patients require insulin for survival, insulin does not provide a cure for this disease or prevent its complications. Despite extensive genetic, molecular, and cellular research on T1D over the years, the translation of this understanding into effective clinical therapies continues to pose a significant obstacle. It is therefore difficult to develop effective clinical treatment strategies without a thorough understanding of disease pathophysiology. Pancreatic tissue bioengineering models of human T1D offer a valuable approach to examining and controlling islet function while tackling various facets of the condition. And in recent years, due to advances in high-throughput omics analysis, the genotypic and molecular profiles of T1D have become finer tuned. The present article will examine recent progress in these areas, along with their utilization and constraints in the realm of T1D.